2012
DOI: 10.1517/13543776.2012.684946
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone secretagogue receptor antagonists

Abstract: The article deals with a patent describing compounds able to interact with ghrelin recepto

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The ghrelinergic system represents a promising pharmacologic target for the treatment of obesity and obesity-related diseases. Indeed, several studies have shown that inhibition of the ghrelin signalling pathway results in a reduction of food intake through decreased appetite and increased energy expenditure and fat catabolism, underlining the potential of ghrelin receptor antagonists, inverse agonist and other strategies targeting the ghrelin hormone in the development of anti-obesity therapeutics (for review see[7], [11][15]). …”
Section: Introductionmentioning
confidence: 99%
“…The ghrelinergic system represents a promising pharmacologic target for the treatment of obesity and obesity-related diseases. Indeed, several studies have shown that inhibition of the ghrelin signalling pathway results in a reduction of food intake through decreased appetite and increased energy expenditure and fat catabolism, underlining the potential of ghrelin receptor antagonists, inverse agonist and other strategies targeting the ghrelin hormone in the development of anti-obesity therapeutics (for review see[7], [11][15]). …”
Section: Introductionmentioning
confidence: 99%